HSP90 Inhibitor Ganetespib (STA-9090) Inhibits Tumor Growth in c-Myc-Dependent Esophageal Squamous Cell Carcinoma - Guan, Liuliu (Onco Targets Ther, 2020)
PURPOSE: Currently, the paucity of classical effective pharmacological drugs to treat esophageal squamous cell carcinoma (ESCC) is a major problem. The c-Myc (MYC) protein is a promising target as it is overexpressed in ESCC. MYC is a sensitive client protein of the heat shock protein 90 (HSP90) and, therefore, targeting the HSP90-MYC axis by inhibition of HSP90 is a potential therapeutic strategy for ESCC. Here, we evaluated the clinical application value of the HSP90 inhibitor (Ganetespib, STA-9090) as an anti-cancer agent for MYC-positive ESCC. MATERIALS AND METHODS: We first analyzed ESCC tissue microarrays and clinical tissue samples to determine MYC expression. The relationship between MYC and HSP90 was analyzed by co-immunoprecipitation assays and immunofluorescence. In in vitro cell models, cell growth was analyzed using the CCK-8 kit, and MYC protein expression was analyzed by Western blot. The in vivo antitumor activity of STA-9090 was assessed in two xenograft animal models. RESULTS: We demonstrated that MYC-overexpressing ESCC cells were highly sensitive to STA-9090 treatment through suppressing ESCC cell proliferation, cell cycle progression and survival. Moreover, STA-9090 treatment decreased MYC expression, reducing the half-life of the MYC protein. We further established two xenograft mouse models using ESCC cells and clinical ESCC samples to validate the effectiveness of STA-9090 in vivo. In both xenograft models, STA-9090 substantially inhibited the growth of MYC-positive ESCC tumors in vivo. In contrast, STA-9090 treatment demonstrated no beneﬁcial effects in mice with low-MYC expressing ESCC tumors. CONCLUSION: In conclusion, our data support that the HSP90 inhibitor, STA-9090, suppresses the expression of the MYC protein and interferes with HSP90-MYC protein–protein interaction. This, in turn, leads to inhibition of ESCC cell proliferation and promotion of apoptosis in ESCC cells in vitro and reduction of ESCC tumors in vivo. We propose, based on our findings, that STA-9090 is a potential novel therapeutic target for MYC-positive ESCC.